Neonatal Immunity, Respiratory Virus Infections, and the Development of Asthma - Restori, Katherine H.; Srinivasa, Bharat T.; Ward, Brian J.; Fixman, Elizabeth D. (Frontiers in Immunology, 2018)
Infants are exposed to a wide range of potential pathogens in the first months of life. Although maternal antibodies acquired transplacentally protect full-term neonates from many systemic pathogens, infections at mucosal surfaces still occur with great frequency, causing significant morbidity and mortality. At least part of this elevated risk is attributable to the neonatal immune system that tends to favour T regulatory (Treg) and Th2 type responses when microbes are first encountered. Early life infection with respiratory viruses is of particular interest because such exposures can disrupt normal lung development and increase the risk of chronic respiratory conditions such as asthma. The immunologic mechanisms that underlie neonatal host-virus interactions that contribute to the subsequent development of asthma have not yet been fully defined. The goals of this review are 1) to outline the differences between the neonatal and adult immune systems; and, 2) to present murine and human data that support the hypothesis that early-life interactions between the immune system and respiratory viruses can create a lung environment conducive to the development of asthma.